Anatomic ACL reconstruction: rectangular tunnel/bone–patellar tendon–bone or triple-bundle/semitendinosus tendon grafting - Shino, Konsei (J Orthop Sci, 2015)
Anatomic ACL reconstruction is the reasonable approach to restore stability without loss of motion after ACL tear. To mimic the normal ACL like a ribbon, our preferred procedures is the anatomic rectangular tunnel (ART) technique with a bone-patellar tendon-bone (BTB) graft or the anatomic triple bundle (ATB) procedure with a hamstring (HS) tendon graft. It is important to create tunnel apertures inside the attachment areas to lessen the tunnel widening. To identify the crescent-shaped ACL femoral attachment area, the upper cartilage margin, the posterior cartilage margin and the resident’s ridge are used as landmarks. To delineate the C-shaped tibial insertion, medial intercondylar ridge, Parson’s knob and anterior horn of the lateral meniscus are helpful. In ART-BTB procedure which is suitable for male patients engaged in contact sports, the parallelepiped tunnels with rectangular apertures are made within the femoral and tibial attachment areas. In ATB-HS technique which is mainly applied to female athletes engaged in non-contact sports including skiing or basketball, 2 femoral and 3 tibial round tunnels are created inside the attachment areas. These techniques make it possible for the grafts to run as the native ACL without impingement to the notch or PCL. After femoral fixation with an interference screw or cortical fixation devices including Endobutton, the graft is pretensioned in situ by repetitive manual pulls at 15–20° of flexion, monitoring the graft tension with tensioners on a tensioning boot installed on the calf. Tibial fixation with pullout sutures is achieved using Double Spike Plate and a screw at the pre-determined amount of tension of 10–20N. While better outcomes with less failure rate are being obtained compared to those in the past, higher graft tear rate remains a problem. Improved preventive training may be required to avoid secondary ACL injuries.